Effect of a 4‐week elastic resistance band training regimen on back kinematics in horses trotting in‐hand and on the lunge. (19th June 2017) - Pfau, T.; Simons, V.; Rombach, N.; Stubbs, N.; Weller, R.
Summary: Background: Training and rehabilitation techniques aiming at improving core muscle strength may result in increased dynamic stability of the equine vertebral column. A system of elastic resistance bands is suggested to provide proprioceptive feedback during motion to encourage recruitment of core abdominal and hindquarter musculature for improved dynamic stability. Objectives: To quantify the effects of a specific resistance band system on back kinematics during trot in‐hand and lungeing at beginning and end of a 4‐week exercise programme. Study design: Quantitative analysis of back movement before/after a 4‐week exercise programme. Methods: Inertial sensor data were collected from seven horses at weeks 1 and 4 of an exercise protocol with elastic resistance bands. Translational (dorsoventral, mediolateral) and rotational (roll, pitch) range of motion of six landmarks from poll to coccygeal region were quantified during trot in‐hand (hard surface) and during lungeing (soft surface, both reins) with/without elastic exercise bands. A mixed model (P<0.05) evaluated the effects of exercise bands, time (week) and movement direction (straight, left, right). Results: The bands reduced roll, pitch and mediolateral displacement in the thoracolumbar region (all P≤0.04). At week 4, independent of band usage, rotational movement (withers, thoracic) was reduced while dorsoventral movement (thoracic, coccygeal) increased. Increased back movement was measured in 80% of back movement parameters during lungeing. Main limitations: Comparing each horse without and with bands without a control group does not distinguish whether the differences measured between weeks 1 and 4 are related to use of the bands, or only to the exercise regimen. Conclusions: Results suggest that the elastic resistance bands reduce mediolateral and rotational movement of the thoracolumbar region (increase dynamic stability) in trot. Further studies should investigate the underlying mechanism with reference to core abdominal and hindquarter muscle recruitment and study the long‐term effects. The Summary is available in Chinese – see Supporting Information.